2009
DOI: 10.1007/s00125-009-1508-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the leptin:adiponectin ratio with measures of insulin resistance in non-diabetic individuals

Abstract: Aims/hypothesisObesity is the dominant cause of insulin resistance. In adult humans it is characterised by a combination of adipocyte hypertrophy and, to a lesser extent, adipocyte hyperplasia. As hypertrophic adipocytes secrete more leptin and less adiponectin, the plasma leptin:adiponectin ratio (LAR) has been proposed as a potentially useful measure of insulin resistance and vascular risk. We sought to assess the usefulness of the LAR as a measure of insulin resistance in non-diabetic white adults.MethodsLe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
224
4
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(263 citation statements)
references
References 16 publications
27
224
4
8
Order By: Relevance
“…When estimates from comparable leptin levels are compared between the two studies, similar results are observed. In addition, associations for the ratio of adiponectin:leptin with endometrial cancer reported in the current study are similar with those reported in B~FIT (13), however continued evaluation is needed to determine if this ratio is indeed a more sensitive measure of insulin resistance, as has been suggested (20)(21), and its relationship with endometrial cancer risk.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…When estimates from comparable leptin levels are compared between the two studies, similar results are observed. In addition, associations for the ratio of adiponectin:leptin with endometrial cancer reported in the current study are similar with those reported in B~FIT (13), however continued evaluation is needed to determine if this ratio is indeed a more sensitive measure of insulin resistance, as has been suggested (20)(21), and its relationship with endometrial cancer risk.…”
Section: Discussionsupporting
confidence: 83%
“…Few studies of adipokines and endometrial cancer risk have included measures of both adiponectin and leptin (8,10,13) and only two have reported associations for their ratio (8,13). The leptin:adiponectin ratio has been suggested to be a surrogate marker of insulin resistance in both diabetic and non-diabetic women (20)(21) and has been shown to be positively associated with breast and colorectal cancer (22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…In this last model, iron depletion reversed these phenotypes [38]. Adipocyte hypertrophy, which is the 'diabetogenic' adipocyte phenotype, is characterised by increased leptin and reduced adiponectin biosynthesis [39]. In the present study, we found that iron administration exerted inverse effects on LEP and ADIPOQ gene expression.…”
Section: Intracellular Iron Deficiency Impairs Adipogenesissupporting
confidence: 56%
“…Moreover, leptin-to-adiponectin ratio has been suggested to be a better marker of cardiovascular disease and type 2 diabetes risk than adiponectin concentration alone 9,10 . In this study, this ratio was unchanged in response to the MedDiet in both sexes, suggesting that the decrease in adiponectin concentration found in response to the MedDiet in men may have, overall, a rather mild negative impact on cardiovascular health.…”
Section: !%" "mentioning
confidence: 99%
“…In the case of leptin, mixed results have been obtained, some studies observed that a high leptin concentration is a predictor of coronary events and type 2 diabetes independently of adiposity 5,6 while others showed that the association between leptin concentrations and these major chronic diseases is largely explained by concomitant variations in body weight or BMI 7,8 . It has been recently suggested that the leptin-to-adiponectin ratio could be a better marker of cardiometabolic alterations and insulin resistance than adiponectin or leptin alone 9,10 .…”
Section: Introductionmentioning
confidence: 99%